SFL pedagogies in language education: Special issue introduction. (February 2022) - Troyan, Francis John; Herazo, José David; Ryshina-Pankova, Marianna
Abstract: The theory and educational practices related to systemic functional linguistics (SFL) originated with the goal of enabling equity and access to the spoken and written texts through which meaning is constructed across linguistic and cultural contexts. SFL was first developed by Michael Halliday and later appropriated by scholars in educational linguistics in Australia . Since that time, this contextualized theory of language and the associated pedagogies have been leveraged by scholars and practitioners in second language (L2) education around the world as a means for developing learners' ability to make meaning in particular communicative contexts. In this tradition, SFL pedagogies have enabled the teaching and learning of written and spoken literacies in a variety of languages; SFL pedagogies represent systematic instruction that develops students' abilities to communicate in a new language within and across cultural contexts and academic content areas. This special issue of System brings together scholars in L2 education from across languages, instructional settings, and national contexts to document the innovative praxis that Halliday's theory has inspired in L2 education. In this introduction to the special issue, we 1) outline the state of the art of SFL Praxis in L2 Education, 2) situate the contributions of this special issue in conversation with the themes identified in the state of the art, and 3) identify future directions for the work in SFL pedagogies in L2 education.